Logical states for fault-tolerant quantum computation with propagating light - Konno, Shunya; Asavanant, Warit; Hanamura, Fumiya; Nagayoshi, Hironari; Fukui, Kosuke; Sakaguchi, Atsushi; Ide, Ryuhoh; China, Fumihiro; Yabuno, Masahiro; Miki, Shigehito; Terai, Hirotaka; Takase, Kan; et al. (Science, 2024)
To harness the potential of a quantum computer, quantum information must be protected against error by encoding it into a logical state that is suitable for quantum error correction. The Gottesman-Kitaev-Preskill (GKP) qubit is a promising candidate because the required multiqubit operations are readily available at optical frequency. To date, however, GKP qubits have been demonstrated only at mechanical and microwave frequencies. We realized a GKP state in propagating light at telecommunication wavelength and verified it through homodyne measurements without loss corrections. The generation is based on interference of cat states, followed by homodyne measurements. Our final states exhibit nonclassicality and non-Gaussianity, including the trident shape of faint instances of GKP states. Improvements toward brighter, multipeaked GKP qubits will be the basis for quantum computation with ligh